Subjective social status and mental health among adolescents in Ethiopia: Evidence from a panel study - Caroline Owens; Craig Hadley (Elsevier, 2023)
Numerous studies have found that a relationship between subjective status and measures of human health persists even after controlling for objective measures, including income, education, and assets. However, few studies have probed how status shapes health among adolescents, particularly those in low-and-middle-income settings. This study examines the relative effects of subjective and objective status on mental health among Ethiopian adolescents. Using data from two waves of the Jimma Longitudinal Family Survey of Youth (N = 1,045), this study uses a combination of linear regression and linear mixed-effects models to examine the relationships between objective social status, subjective social status, and mental well-being among adolescents in Ethiopia. Three measures of objective status, including household income, adolescent education, and a multidimensional measure of material wealth, were assessed. Social network and support variables were constructed using factor analysis. A community version of the 10-rung McArthur ladder was used to assess the subjective socioeconomic status of adolescents. The self-reporting questionnaire was used to assess mental well-being during both waves of the study. The significant effect of higher subjective status on reports of fewer non-specific psychological distress (−0.28; 95% CI: −0.43 to −0.14) was not mediated by objective status, material deprivation, or social support covariates. The observed relationship between status and mental well-being was consistent across successive study waves. Among a cohort of adolescents in Jimma, Ethiopia, several measures of objective status are associated with subjective status. However, akin to research among adults, the findings of our study suggest that the relationship between adolescent subjective social status and mental health persists above and beyond the effects of objective status. Future research is needed on the factors, environments, and experiences that inform adolescent perceptions of status and well-being over time.